Using physical education to promote out-of school physical activity in lower secondary school students - a randomized controlled trial protocol - Juho Polet; Mary Hassandra; Taru Lintunen; Arto Laukkanen; Nelli Hankonen; Mirja Hirvensalo; Tuija Tammelin; Martin S. Hagger (BMC, 2019)
Abstract Background Given the documented decline in levels of physical activity in early adolescence, promoting physical activity in young people is a priority for health promotion. School physical education (PE) is an important existing network in which participation in physical activity beyond school can be promoted to the captive young people. The objective of current article is to present the protocol for a PE teacher-delivered theory-based trial to promote secondary school students' participation in physical activity out-of-school contexts. The intervention will be guided by the trans-contextual model explaining the processes by which PE teachers' support for autonomous motivation in the classroom promotes students' motivation to engage in out-of-school physical activity. We hypothesize that school students receiving the teacher-delivered intervention to promote autonomous motivation toward physical activity will exhibit greater participation in physical activities outside of school, relative to students receiving a control intervention. Methods The trial will adopt a waitlist-control design with cluster-randomization by school. PE teachers assigned to the intervention condition will receive a two-week, 12-h training program comprising basic information on how to promote out-of-school physical activity and theory-based training on strategies to promote students' autonomous motivation toward physical activity. Teachers assigned to the waitlist control condition will receive an alternative training on how to monitor physical functional capacity in children with special needs. PE teachers (n = 29) from eleven schools will apply the intervention program to students (n = 502) in PE classes for one month. Physical activity participation, the primary outcome variable, and psychological mediators from the trans-contextual model will be measured at pre-trial, post-trial, and at one-, three- and six-months post-trial. We will also assess teachers' autonomy-supportive techniques and behaviours by observation. Discussion The study will make a unique contribution to the literature by testing a theory-based intervention delivered by PE teachers to promote school students' participation in out-of-school physical activity. Information will be useful for educators, community stakeholders and policy makers interested in developing programs to promote students' out-of-school physical activity. Trial registration ISRCTN39374060. Registered 19.7.2018.